A kind of biomass porous carbon for CO2 adsorption and preparation method thereof

By treating lotus stems with dilute acid and concentrated alkali, mixing them with chitosan and potassium oxalate, biomass porous carbon with high specific surface area and excellent CO2 adsorption performance is prepared, solving the problems of complex process and insufficient adsorption performance in the prior art.

CN118164483BActive Publication Date: 2025-04-01SICHUAN UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410270702.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-11
Publication Date
2025-04-01
Estimated Expiration
2044-03-11

AI Technical Summary

Technical Problem

The preparation process of biomass activated carbon used for CO2 adsorption in the prior art is complex, and the adsorption performance needs to be further improved.

Method used

The lotus stems were soaked with dilute acid and concentrated alkali to remove impurities and lignin. The lotus stem powder was then mixed with chitosan and potassium oxalate, and then carbonized and washed to obtain biomass porous carbon for CO2 adsorption.

Benefits of technology

The specific surface area and pore structure of activated carbon are improved, the adsorption capacity to CO2 is enhanced, and the excellent CO2 adsorption amount and selectivity are achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118164483B_ABST
    Figure CN118164483B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing biomass porous carbon for CO2 adsorption, comprising the following steps: S1, soaking lotus stems in dilute acid to remove impurities, soaking the lotus stems in concentrated alkali again to remove part of lignin, washing with water for neutralization, and powdering the treated lotus stems to 150-200 meshes; S2, mixing lotus stem powder in ethanol at a certain temperature; using lotus stem powder, nitrogen doping agent and activating agent in a certain mass ratio as raw materials, chitosan as the nitrogen doping agent, introducing nitrogen elements to increase the alkaline sites on the surface of activated carbon, wherein the alkaline sites are conducive to the adsorption of CO2, potassium oxalate as the activating agent, which can promote the pore formation and activation of lotus stem powder in the carbonization process, increase the pore structure of activated carbon, provide more adsorption sites, and the synergistic effect of the lotus stem powder, the nitrogen doping agent and the activating agent jointly promotes the pore structure development and surface property optimization of the activated carbon, so that the activated carbon has excellent CO2 adsorption capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of nitrogen-containing activated carbon preparation, and in particular to a biomass porous carbon for CO2 adsorption and a preparation method thereof. Background Art

[0002] With the development of the industrial revolution and construction technology, the combustion of fossil raw materials brings about a large amount of harmful gases, mainly CO2. Carbon dioxide is the main component of greenhouse gases and causes a series of harms to the environment. For example, it will lead to rising global temperatures, melting glaciers, rising sea levels and reduced agricultural production. Therefore, there is an urgent need to develop effective strategies to reduce carbon dioxide emissions. Carbon dioxide capture and storage (CCS) is considered to be an effective solution to reduce carbon dioxide emissions. At present, amine washing, membrane separation, and ionic liquid absorption are commonly used methods for carbon capture and storage. Compared with these methods, solid adsorbents have the advantages of low pollution, low energy consumption, easy operation, and no corrosion.

[0003] Every year, a large amount of agricultural and forestry waste is generated around the world, posing a major challenge to the environment. The main method of dealing with these wastes is incineration, which not only causes environmental pollution but also wastes precious resources. Lotus, as a well-known aquatic plant, has high ornamental and edible value, while its lotus stem is an agricultural residue with limited value. Considering the advantages of lotus stem being widely available and low cost, it can be used as an ideal precursor for the preparation of activated carbon.

[0004] The Chinese invention patent with patent number CN106517181A discloses a method for preparing biomass-based activated carbon with high CO2 adsorption efficiency, and the steps are as follows: crushed peanut shells, walnut shells or pecan shells are first activated by hydrothermal method, and then carbonized in N2 atmosphere, and the carbonized material is repeatedly washed with 0.1mol / L hydrochloric acid and distilled water until neutral, and then dried to obtain activated carbon. The high specific surface area activated carbon prepared by the invention has excellent adsorption performance and stable cyclic regeneration adsorption performance for CO2 at room temperature and pressure. However, the process of the above patent is hydrothermal first, then carbonization, and the process is complicated.

[0005] Therefore, it is necessary to improve the deficiencies in the prior art to solve the above problems. Summary of the invention

[0006] The present invention overcomes the deficiencies of the prior art and provides a biomass porous carbon for CO2 adsorption and a preparation method thereof.

[0007] To achieve the above object, the technical solution adopted by the present invention is: a method for preparing biomass porous carbon for CO2 adsorption, comprising the following steps:

[0008] S1, soaking the lotus stems in dilute acid to remove impurities, soaking the lotus stems in concentrated alkali to remove part of the lignin, washing with water to neutralize, and powdering the treated lotus stems to 150-200 mesh;

[0009] S2, mixing the lotus stem powder in ethanol, stirring at a certain temperature to separate flavonoids and polyphenol compounds, filtering and concentrating to obtain a concentrated solution of flavonoids and polyphenol compounds, and lotus stem residue;

[0010] S3, adding water to the lotus stem residue, nitrogen doping agent and activator in a certain mass ratio and mixing them evenly, and drying them at a temperature of 50-70°C for 8-12h;

[0011] S4, carbonizing the product in S3 at a temperature of 500-900°C;

[0012] S5. Wash the product in S4 with 1 mol / L hydrochloric acid and water in turn, soak it in a concentrated solution of flavonoids and polyphenols with a concentration of 8-15 wt%, and dry it at 80-90°C for 4-6 hours to obtain biomass porous carbon for CO2 adsorption.

[0013] In a preferred embodiment of the present invention, in step S1, the dilute acid is hydrochloric acid with a concentration of 5-8wt%, and the concentrated alkali is one of potassium hydroxide or sodium hydroxide with a concentration of 5-8wt%.

[0014] In a preferred embodiment of the present invention, in step S1, the soaking is carried out at a temperature of 40-50° C. for 1-2 hours.

[0015] In a preferred embodiment of the present invention, in step S2, stirring is performed at a temperature of 60-80° C. for 1-2 h.

[0016] In a preferred embodiment of the present invention, in step S3, the nitrogen-doping agent is chitosan, and the activating agent is potassium oxalate.

[0017] In a preferred embodiment of the present invention, the mass ratio of the lotus stem powder to the chitosan and the potassium oxalate is 1:0-2:0-3.

[0018] In a preferred embodiment of the present invention, in the step S4, the carbonization is carried out in a nitrogen environment, the heating rate is 2-8°C / min, and the carbonization time is 0.5-3h.

[0019] In a preferred embodiment of the present invention, in step S5, the soaking is carried out at a temperature of 40-60° C. for 2-5 hours.

[0020] The present invention provides a biomass porous carbon for CO2 adsorption, and the biomass porous carbon for CO2 adsorption is prepared by the above-mentioned preparation method.

[0021] In a preferred embodiment of the present invention, the specific surface area of ​​the biomass porous carbon used for CO2 adsorption is 429-2630m 2 / g, CO2 adsorption capacity is 2.23-4.59mmol / g.

[0022] The present invention solves the defects existing in the background technology and has the following beneficial effects:

[0023] (1) The present invention provides a biomass porous carbon for CO2 adsorption and a preparation method thereof. Lotus stem powder, a nitrogen doping agent and an activating agent in a certain mass ratio are used as raw materials, chitosan is used as a nitrogen doping agent, and nitrogen elements are introduced to increase the alkaline sites on the surface of activated carbon. The alkaline sites are beneficial to the adsorption of CO2. Potassium oxalate is used as an activating agent to promote the pore formation and activation of lotus stem powder during the carbonization process, increase the pore structure of activated carbon, and further provide more adsorption sites. The synergistic effect of lotus stem powder, nitrogen doping agent and activating agent can jointly promote the development of the pore structure of activated carbon and the optimization of surface properties, so that it has excellent CO2 adsorption capacity.

[0024] (2) In the present invention, the lotus stem is pulverized into 150-200 meshes. The finer lotus stem powder has a larger specific surface area, and can form more micropores and mesopores during the carbonization process, providing more active sites for the adsorption of activated carbon. At the same time, chitosan can introduce nitrogen-containing functional groups to the surface of the activated carbon during the carbonization process, which not only increases the polarity of the activated carbon surface, but also provides additional adsorption sites. If the lotus stem powder is too fine, it will cause the collapse or blockage of the pore structure during the carbonization process. If the proportion of chitosan is too high, it will also occupy too many pores, reducing the specific surface area and adsorption performance of the activated carbon. By appropriately adjusting the mesh size of the lotus stem powder and the proportion of chitosan, the biomass porous carbon of the present invention can have a high specific surface area, a rich pore structure and excellent adsorption performance for CO2.

[0025] (3) In the present invention, the lotus stems are first soaked with dilute acid and concentrated alkali in sequence. The dilute acid can effectively dissolve and remove inorganic salts and minerals in the lotus stems, which helps to reduce the ash content in the final porous carbon and improve the purity of the carbon. At the same time, it can protect cellulose to a certain extent to avoid excessive degradation in subsequent treatments. The concentrated alkali can react with the lignin in the lotus stems again, causing the lignin to hydrolyze, degrade or swell, thereby making the lotus stem structure looser, thereby helping to form a richer pore structure in the subsequent carbonization process and improving the specific surface area and pore volume of the porous carbon.

[0026] (4) In the present invention, the concentrated solution of extracted flavonoids and polyphenols is soaked with the product after carbonization and washing. Since flavonoids and polyphenols contain multiple functional groups such as -OH and C=O, they can form hydrogen bonds or van der Waals interactions with CO2 molecules, thereby increasing the adsorption capacity of CO2. Since the presence of these compounds can change the polarity of the surface of the activated carbon material, these compounds are introduced into the activated carbon material, which is equivalent to adding additional adsorption sites on the carbon skeleton.

[0027] (5) In the present invention, the natural biomass material lotus stem is used as the raw material. The lotus stem itself is rich in functional groups such as -OH, -COOH, and -Ar-OH. The -OH polar functional group can form hydrogen bonds with polar molecules, the -COOH acidic functional group can adsorb metal ions or other polar molecules by ion exchange or chemical bond formation, and the -Ar-OH polar functional group can form hydrogen bonds with the adsorbate, thereby enhancing the adsorption effect. The prepared activated carbon material contains more surface oxygen-containing functional groups and has better adsorption performance. At the same time, the lotus stem, as a renewable resource, has the advantages of wide sources and low prices. It can not only realize the effective utilization of resources, but also reduce production costs, and has environmental protection and economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art are briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative work.

[0029] Figure 1 It is a flow chart of a method for preparing biomass porous carbon for CO2 adsorption according to a preferred embodiment of the present invention. DETAILED DESCRIPTION

[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein. Therefore, the protection scope of the present invention is not limited to the specific embodiments disclosed below.

[0032] It should be noted that the raw materials, equipment and reagents used in the present invention can be purchased from the market or obtained by the preparation methods of the existing technology, and will not be described in detail here.

[0033] like Figure 1 As shown, a method for preparing biomass porous carbon for CO2 adsorption comprises the following steps:

[0034] S1, soaking the lotus stems in dilute acid to remove impurities, soaking the lotus stems in concentrated alkali to remove part of the lignin, washing with water to neutralize, and powdering the treated lotus stems to 150-200 mesh;

[0035] S2. Mixing the lotus stem powder in ethanol, stirring at a certain temperature to separate flavonoids and polyphenol compounds, filtering and concentrating to obtain a concentrated solution of flavonoids and polyphenol compounds and lotus stem residue.

[0036] S3, adding water to the lotus stem residue, nitrogen doping agent and activator in a certain mass ratio and mixing them evenly, and drying them at a temperature of 50-70°C for 8-12h;

[0037] S4, carbonizing the product in S3 at a temperature of 500-900°C;

[0038] S5. Wash the product in S4 with 1 mol / L hydrochloric acid and water in turn, soak it in a concentrated solution of flavonoids and polyphenols with a concentration of 8-15 wt%, and dry it at 80-90°C for 4-6 hours to obtain biomass porous carbon for CO2 adsorption.

[0039] In step S1 of the present invention, the diluted acid is hydrochloric acid with a concentration of 5-8wt%, and the concentrated alkali is potassium hydroxide or sodium hydroxide with a concentration of 5-8wt%; the soaking is carried out at a temperature of 40-50°C for 1-2h.

[0040] It should be noted that, by first soaking the lotus stems with dilute acid and concentrated alkali in sequence, the dilute acid can effectively dissolve and remove inorganic salts and minerals in the lotus stems, which helps to reduce the ash content in the final porous carbon and improve the purity of the carbon. At the same time, it can protect cellulose to a certain extent to avoid excessive degradation in subsequent treatments. The concentrated alkali can react with the lignin in the lotus stems again, causing the lignin to hydrolyze, degrade or swell, thereby making the lotus stem structure looser, which helps to form a richer pore structure in the subsequent carbonization process and improve the specific surface area and pore volume of the porous carbon.

[0041] In step S2 of the present invention, stirring is performed at a temperature of 60-80° C. for 1-2 hours.

[0042] It should be noted that in step S2, after obtaining flavonoids and polyphenol compounds, the lotus stem residue and the ethanol solution containing flavonoids and polyphenol compounds are separated by filtration to obtain lotus stem residue, and the ethanol solution containing flavonoids and polyphenol compounds is evaporated at a temperature of 120-150° C. for 0.5-2 h to obtain a concentrated solution of flavonoids and polyphenol compounds.

[0043] In step S3 of the present invention, the nitrogen doping agent is chitosan, the activating agent is potassium oxalate, and the mass ratio of lotus stem powder to chitosan and potassium oxalate is 1:0-2:0-3.

[0044] In step S4 of the present invention, carbonization is carried out in a nitrogen environment, and the carbonization time is 0.5-3h; the heating rate of carbonization is 2-8°C / min; at a suitable carbonization temperature and time, the organic matter in the lotus stem undergoes a pyrolysis reaction at a high temperature to form a porous carbon structure, and as the heating rate increases, the carbonization temperature increases, the connection between the carbon atoms becomes tighter, forming a more ordered carbon lattice structure, improving the mechanical strength and chemical stability of the activated carbon, and causing the surface functional groups to undergo a certain degree of pyrolysis or rearrangement, thereby adjusting the surface polarity and chemical activity of the activated carbon.

[0045] In step S5 of the present invention, the soaking is carried out at a temperature of 40-60° C. for 2-5 hours.

[0046] The present invention provides a biomass porous carbon for CO2 adsorption, which is prepared by the above-mentioned preparation method. The specific surface area of ​​the biomass porous carbon for CO2 adsorption is 429-2630m 2 / g, CO2 adsorption capacity is 2.23-4.59mmol / g.

[0047] Example 1

[0048] A method for preparing biomass porous carbon for CO2 adsorption comprises the following steps:

[0049] S1. Using 6wt% hydrochloric acid, soak the lotus stems at 40°C for 1h to remove impurities, using 6wt% potassium hydroxide again, soak the lotus stems at 40°C for 1h to remove part of the lignin, washing with water to neutralize, and powdering the treated lotus stems to 160 mesh;

[0050] S2, mixing the lotus stem powder in ethanol, stirring at a temperature of 60° C. for 2 h, separating flavonoids and polyphenolic compounds, separating the lotus stem residue from the ethanol solution containing flavonoids and polyphenolic compounds by filtering to obtain lotus stem residue, and evaporating the ethanol solution containing flavonoids and polyphenolic compounds at a temperature of 120° C. for 1.5 h to obtain a concentrated solution of flavonoids and polyphenolic compounds;

[0051] S3, adding water to the lotus stem residue, chitosan and potassium oxalate in a mass ratio of 1:1:2 and mixing them evenly, and then drying them at a temperature of 60°C for 10 hours;

[0052] S4, heating the product in S3 to 700°C at a rate of 5°C / min in a nitrogen atmosphere and maintaining the temperature for 1 hour to complete carbonization;

[0053] S5. Wash the product in S4 with 1 mol / L hydrochloric acid and water in turn, soak it in a 12 wt% concentrated solution of flavonoids and polyphenols at 50°C for 4 h, and then dry it at 80°C for 4 h to obtain biomass porous carbon.

[0054] The specific surface area of ​​the obtained biomass porous carbon is 1873m 2 / g, and the nitrogen content is 2.68wt%.

[0055] Example 2

[0056] This embodiment is substantially the same as Embodiment 1, except that in step S3, the mass ratio of lotus stem powder to chitosan and potassium oxalate is 1:2:2.

[0057] The specific surface area of ​​the obtained biomass porous carbon is 2131m 2 / g, and the nitrogen content is 2.77wt%.

[0058] Example 3

[0059] This embodiment is substantially the same as Embodiment 1, except that in step S3, the mass ratio of lotus stem powder to chitosan and potassium oxalate is 1:0.5:2.

[0060] The specific surface area of ​​the obtained biomass porous carbon is 1374m 2 / g, and the nitrogen content is 2.32wt%.

[0061] Example 4

[0062] This embodiment is substantially the same as Embodiment 1, except that in step S3, the mass ratio of lotus stem powder to chitosan and potassium oxalate is 1:1:3.

[0063] The specific surface area of ​​the obtained biomass porous carbon is 953m 2 / g, and the nitrogen content is 2.41wt%.

[0064] Example 5

[0065] This embodiment is substantially the same as Embodiment 1, except that in step S3, the mass ratio of lotus stem powder to chitosan and potassium oxalate is 1:1:1.

[0066] The specific surface area of ​​the obtained biomass porous carbon is 1252m 2 / g, and the nitrogen content is 2.62wt%.

[0067] Example 6

[0068] This embodiment is substantially the same as Embodiment 1, except that in step S3, the mass ratio of lotus stem powder to chitosan and potassium oxalate is 1:0:2.

[0069] The specific surface area of ​​the obtained biomass porous carbon is 429m 2 / g, and the nitrogen content is 1.02wt%.

[0070] Example 7

[0071] This embodiment is substantially the same as Embodiment 1, except that in step S3, the mass ratio of lotus stem powder to chitosan and potassium oxalate is 1:1:0.

[0072] The specific surface area of ​​the obtained biomass porous carbon is 522 m 2 / g, and the nitrogen content is 1.12wt%.

[0073] Example 8

[0074] This embodiment is substantially the same as Embodiment 1, except that in step S3, the mass ratio of lotus stem powder to chitosan and potassium oxalate is 1:1.5:2.

[0075] The specific surface area of ​​the obtained biomass porous carbon is 2168m 2 / g, and the nitrogen content is 2.62wt%.

[0076] Adsorption characteristics test steps: The adsorption amount of CO2 at different temperatures was measured by static adsorption experiments on an automatic gas adsorption instrument (Autosorb iQ, Quantachrome Corp., US). Before the measurement, Examples 1-8 were degassed at 300°C in vacuum for 6 hours. The adsorption amount of N2 at 25°C was also measured by static adsorption experiments on an automatic gas adsorption instrument. The selectivity of the adsorbent for CO2 at 25°C was calculated by the following formula: S(CO2 / N2)=(q1 / q2) / (x1 / x2), wherein q1 is the adsorption amount of CO2 at 0.15 bar, q2 is the adsorption amount of N2 at 0.75 bar, x1 is the partial pressure of CO2 of 0.15 bar, and x2 is the partial pressure of N2 of 0.75 bar. After completing an adsorption experiment, Examples 1-9 were evacuated to less than 1*10 -4 bar, and immediately conduct the second adsorption experiment, which is repeated 5 times.

[0077] The adsorption amount of CO2 by the biomass porous carbon prepared in Examples 1-8 was measured respectively, and the practical results are shown in Table 1.

[0078] Table 1:

[0079]

[0080] Conclusion: By comparing Examples 1 and 8 with Examples 7 and 8, it can be learned that by using lotus stem powder, nitrogen doping agent and activator in a certain mass ratio as raw materials, chitosan is used as a nitrogen doping agent to introduce nitrogen elements to increase the alkaline sites on the surface of activated carbon, and the alkaline sites are conducive to the adsorption of CO2. Potassium oxalate is used as an activator to promote the pore formation and activation of lotus stem powder during the carbonization process, increase the pore structure of activated carbon, and provide more adsorption sites. The synergistic effect of lotus stem powder, nitrogen doping agent and activator can jointly promote the development of the pore structure of activated carbon and the optimization of surface properties, so that it has excellent CO2 adsorption capacity.

[0081] By comparing Example 1 and Example 2, it can be seen that when the proportion of chitosan is increased and the nitrogen content in the activated carbon exceeds the figure of merit, the surface of the activated carbon will be too crowded, so that some nitrogen atoms cannot effectively interact with CO2 molecules, and more tar or other by-products may be produced during the pyrolysis process, blocking the pores of the activated carbon, causing some pore structures to become smaller or the pores to be closed, thereby affecting its adsorption performance.

[0082] By comparing Example 1 and Example 3, it can be seen that when the proportion of chitosan is reduced beyond the optimum value, the nitrogen content in the activated carbon will be insufficient, which will reduce the surface polarity of the activated carbon. The lack of nitrogen element reduces the chance of forming chemical bonds with CO2 molecules and reduces the adsorption capacity.

[0083] By comparing Example 1 and Example 4, it can be seen that when the proportion of potassium oxalate is increased beyond the optimum value, it may lead to over-activation of the activated carbon, making the pore structure too developed, or even forming large pores or broken structures, causing the pore walls to become thinner or even collapse, which in turn reduces the specific surface area of ​​the activated carbon and reduces the adsorption sites.

[0084] By comparing Example 1 and Example 5, it can be seen that when the proportion of potassium oxalate is reduced beyond the optimum value, it will lead to insufficient activation of the activated carbon, insufficient development of the pore structure, smaller specific surface area and pore volume, and reduced adsorption performance.

[0085] Example 9

[0086] This embodiment is basically the same as Embodiment 8, except that in step S1, the lotus stem is powdered to 150 mesh.

[0087] The specific surface area of ​​the obtained biomass porous carbon is 1752m 2 / g, and the nitrogen content is 2.55wt%.

[0088] Example 10

[0089] This embodiment is basically the same as Embodiment 8, except that in step S1, the lotus stem is powdered to 180 mesh.

[0090] The specific surface area of ​​the obtained biomass porous carbon is 2428m 2 / g, and the nitrogen content is 2.61wt%.

[0091] Embodiment 11

[0092] This embodiment is substantially the same as Embodiment 8, except that in step S1, the lotus stem is powdered to a size of 200 mesh.

[0093] The specific surface area of ​​the obtained biomass porous carbon is 1568m 2 / g, and the nitrogen content is 2.49wt%.

[0094] Example 12

[0095] This embodiment is basically the same as Embodiment 8, except that in step S1, the lotus stem is powdered to 140 mesh.

[0096] The specific surface area of ​​the obtained biomass porous carbon is 681m 2 / g, and the nitrogen content is 2.15wt%.

[0097] Embodiment 13

[0098] This embodiment is basically the same as Embodiment 8, except that in step S1, the lotus stem is powdered to 210 mesh.

[0099] The specific surface area of ​​the obtained biomass porous carbon is 1293m 2 / g, and the nitrogen content is 1.97wt%.

[0100] Adsorption characteristics test steps: The adsorption amount of CO2 at different temperatures was measured by static adsorption experiments on an automatic gas adsorption instrument (Autosorb iQ, Quantachrome Corp., US). Before the measurement, Examples 9-13 were all degassed at 300°C in vacuum for 6 hours. The adsorption amount of N2 at 25°C was also measured by static adsorption experiments on an automatic gas adsorption instrument. The selectivity of the adsorbent for CO2 at 25°C was calculated by the following formula: S(CO2 / N2)=(q1 / q2) / (x1 / x2), where q1 is the adsorption amount of CO2 at 0.15 bar, q2 is the adsorption amount of N2 at 0.75 bar, x1 is the partial pressure of CO2 of 0.15 bar, and x2 is the partial pressure of N2 of 0.75 bar. After completing an adsorption experiment, Examples 9-13 were evacuated to less than 1*10 -4 bar, and immediately conduct the second adsorption experiment, which is repeated 5 times.

[0101] The adsorption capacity of CO2 by the biomass porous carbon prepared in Examples 9-13 was measured respectively, and the practical results are shown in Table 2.

[0102] Table 2:

[0103]

[0104] Conclusion: It can be seen from Example 10 that finer lotus stem powder has a larger specific surface area and can form more micropores and mesopores during the carbonization process, providing more active sites for the adsorption of activated carbon.

[0105] By comparing Example 8 with Example 11 and Example 13, it can be seen that if the lotus stem powder is too fine, it will cause the collapse or blockage of the pore structure during the carbonization process, thereby affecting its adsorption performance.

[0106] By comparing Example 8 with Example 9 and Example 12, it can be seen that the lotus stem powder is too coarse and has a small specific surface area, which limits the reaction area with chitosan and potassium oxalate, easily leading to insufficient development of the pore structure, forming fewer micropores and mesopores, and reducing the adsorption performance of the activated carbon.

[0107] Embodiment 14

[0108] This embodiment is substantially the same as Embodiment 10, except that in step S3, the mass ratio of lotus stem powder to chitosan is 1:1.

[0109] The specific surface area of ​​the obtained biomass porous carbon is 1924m 2 / g, and the nitrogen content is 2.17wt%.

[0110] Embodiment 15

[0111] This embodiment is substantially the same as Embodiment 10, except that in step S3, the mass ratio of lotus stem powder to chitosan is 1:1.3.

[0112] The specific surface area of ​​the obtained biomass porous carbon is 2171m 2 / g, and the nitrogen content is 2.31wt%.

[0113] Example 16

[0114] This embodiment is substantially the same as Embodiment 10, except that in step S3, the mass ratio of lotus stem powder to chitosan is 1:1.8.

[0115] The specific surface area of ​​the obtained biomass porous carbon is 2630m 2 / g, and the nitrogen content is 2.81wt%.

[0116] Embodiment 17

[0117] This embodiment is substantially the same as Embodiment 10, except that in step S3, the mass ratio of lotus stem powder to chitosan is 1:2.

[0118] The specific surface area of ​​the obtained biomass porous carbon is 1927m 2 / g, and the nitrogen content is 2.59wt%.

[0119] Embodiment 18

[0120] This embodiment is basically the same as embodiment 10, except that: there is no step S2; in step S3, the lotus stem residue is the lotus stem powder of S1; in step S5, there is no soaking in a concentrated solution of flavonoids and polyphenols with a concentration of 12wt% at a temperature of 50°C for 4h.

[0121] The specific surface area of ​​the obtained biomass porous carbon is 573m 2 / g, and the nitrogen content is 2.24wt%.

[0122] Adsorption characteristics test steps: The adsorption amount of CO2 at different temperatures was measured by static adsorption experiments on an automatic gas adsorption instrument (Autosorb iQ, Quantachrome Corp., US). Before the measurement, Examples 14-17 were all degassed at 300°C in vacuum for 6 hours. The adsorption amount of N2 at 25°C was also measured by static adsorption experiments on an automatic gas adsorption instrument. The selectivity of the adsorbent for CO2 at 25°C was calculated by the following formula: S(CO2 / N2)=(q1 / q2) / (x1 / x2), wherein q1 is the adsorption amount of CO2 at 0.15 bar, q2 is the adsorption amount of N2 at 0.75 bar, x1 is the partial pressure of CO2 of 0.15 bar, and x2 is the partial pressure of N2 of 0.75 bar. After completing an adsorption experiment, Examples 14-17 were evacuated to less than 1*10 -4 bar, and immediately conduct the second adsorption experiment, which is repeated 5 times.

[0123] The adsorption amount of CO2 by the biomass porous carbon prepared in Examples 14-17 was measured respectively, and the practical results are shown in Table 3.

[0124] Table 3:

[0125]

[0126] Conclusion: By comparing Example 10 with Example 14, Example 15, Example 16 and Example 17, it can be learned that when the mesh size of the lotus stem powder and the ratio of the lotus stem powder to chitosan are matched and combined, more micropores and mesopores can be formed. These pore structures are very beneficial for the adsorption of small molecules such as CO2, and may also increase the adsorption rate and capacity of the activated carbon, so that it can reach a higher adsorption amount in a short time. The mesh size of the lotus stem powder and an inappropriate ratio may lead to a decrease in the performance of the activated carbon. By adjusting the mesh size of the lotus stem powder and the ratio of chitosan, the biomass porous carbon of the present invention can have a high specific surface area, rich pore structure and excellent adsorption performance for CO2.

[0127] By comparing Example 10 and Example 18, it can be seen that by soaking the concentrated solution of extracted flavonoids and polyphenols with the product after carbonization washing, since flavonoids and polyphenols contain multiple functional groups such as -OH, C=O, etc., they can form hydrogen bonds or van der Waals interactions with CO2 molecules, thereby increasing the adsorption capacity for CO2. In addition, since the presence of these compounds can change the polarity of the surface of the activated carbon material, introducing these compounds into the activated carbon material is equivalent to adding additional adsorption sites on the carbon skeleton, which can make its adsorption performance for CO2 even better.

[0128] The above is based on the ideal embodiment of the present invention. Through the above description, it is obvious to those skilled in the art that the present invention is not limited to the details of the above exemplary embodiments, and the present invention can be implemented in other specific forms without departing from the spirit or basic characteristics of the present invention. Therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive. The scope of the present invention is limited by the attached claims rather than the above description, and it is intended to include all changes within the meaning and scope of the equivalent elements of the claims. Any figure mark in the claims should not be regarded as limiting the claims involved.

[0129] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for preparing biomass porous carbon for CO2 adsorption, characterized in that: The following steps are involved: S1, soaking the lotus stems in dilute acid to remove impurities, then soaking the lotus stems in concentrated alkali to remove part of the lignin, washing with water to neutralize, and powdering the treated lotus stems to 150-200 mesh; S2, mixing the lotus stem powder in ethanol, stirring at a certain temperature to separate polyphenol compounds, filtering and concentrating to obtain a concentrated solution of polyphenol compounds and lotus stem residue; S3, adding water to the lotus stem residue, nitrogen doping agent and activator in a certain mass ratio and mixing them evenly, and drying them at a temperature of 50-70°C for 8-12h; S4, carbonizing the product in S3 at a temperature of 500-900°C; S5. Wash the product in S4 with 1 mol / L hydrochloric acid and water in turn, soak it in a concentrated solution of polyphenol compounds with a concentration of 8-15 wt%, and dry it at a temperature of 80-90° C. for 4-6 hours to obtain biomass porous carbon for CO2 adsorption.

2. The method for preparing biomass porous carbon for CO2 adsorption according to claim 1, characterized in that: In the step S1, the dilute acid is hydrochloric acid with a concentration of 5-8wt%, and the concentrated alkali is one of potassium hydroxide or sodium hydroxide with a concentration of 5-8wt%.

3. The method for preparing biomass porous carbon for CO2 adsorption according to claim 1, characterized in that: In the step S1, the soaking is carried out at a temperature of 40-50° C. for 1-2 hours.

4. The method for preparing biomass porous carbon for CO2 adsorption according to claim 1, characterized in that: In the step S2, stirring is performed at a temperature of 60-80° C. for 1-2 h.

5. The method for preparing biomass porous carbon for CO2 adsorption according to claim 1, characterized in that: In step S3, the nitrogen-doping agent is chitosan, and the activating agent is potassium oxalate.

6. The method for preparing biomass porous carbon for CO2 adsorption according to claim 5, characterized in that: The mass ratio of the lotus stem powder to the chitosan and the potassium oxalate is 1:0-2:0-3.

7. The method for preparing biomass porous carbon for CO2 adsorption according to claim 1, characterized in that: In the step S4, the carbonization is carried out in a nitrogen environment, the heating rate is 2-8°C / min, and the carbonization time is 0.5-3h.

8. The method for preparing biomass porous carbon for CO2 adsorption according to claim 1, characterized in that: In the step S5, the soaking is carried out at a temperature of 40-60° C. for 2-5 hours.

9. A biomass porous carbon for CO2 adsorption, characterized in that: The biomass porous carbon for CO2 adsorption is obtained by the preparation method described in any one of claims 1-8.

10. The biomass porous carbon for CO2 adsorption according to claim 9, characterized in that: The specific surface area of ​​the biomass porous carbon for CO2 adsorption is 429-2630m 2 / g, CO2 adsorption capacity is 2.23-4.59mmol / g.

Citation Information

Patent Citations

  • Preparation method of biomass based activated carbon with high CO2 adsorption efficiency

    CN106517181A

  • Resource utilization method of camellia oleifera shells

    CN103030710A

  • Novel method of comprehensively utilizing cotton stalks

    CN103540692A